An Overview on the Conversion of Forest Biomass into Bioenergy - Yu, Qing; Wang, Yacheng; Van Le, Quyet; Yang, Han; Hosseinzadeh-Bandbafha, Homa; Yang, Yafeng; Sonne, Christian; Tabatabaei, Meisam; Lam, Su Shiung; Peng, Wanxi (Frontiers in Energy Research, 2021)
Biomass plays a crucial role in mitigating the concerns associated with increasing fossil fuel combustion. Among various types of biomass, forest biomass has attracted considerable attention given its abundance and variations. In this work, an overview is presented on different pathways available to convert forest biomass into bioenergy. Direct use of forest biomass could reduce carbon dioxide emissions associated with conventional energy production systems. However, there are certain drawbacks to the direct use of forest biomass, such as low energy conversion rate and soot emissions and residues. Also, lack of continuous access to biomass is a severe concern in the long-term sustainability of direct electricity generation by forest biomass. To solve this problem, co-combustion with coal, as well as pelletizing of biomass, are recommended. The co-combustion of forest biomass and coal could reduce carbon monoxide, nitrogen oxides, and sulfide emissions of the process. Forest biomass can also be converted into various liquid and gaseous biofuels through biochemical and thermochemical processes, which are reviewed and discussed herein. Despite the favorable features of forest biomass conversion processes to bioenergy, their long-term sustainability should be more extensively scrutinized by future studies using advanced sustainability assessment tools such as life cycle assessment, exergy, etc.